Efficiency of ablative plasma energy transfer into a massive aluminum target using different atomic number ablators. (30th April 2015) - Kasperczuk, A.; Pisarczyk, T.; Chodukowski, T.; Kalinowska, Z.; Stepniewski, W.; Jach, K.; Swierczynski, R.; Renner, O.; Smid, M.; Ullschmied, J.; Cikhardt, J.; Klir, D.; et al.
Abstract This paper aims at investigation of efficiency of an ablative plasma energy transfer into a massive aluminum target using different atomic number ablators. For this reason, several target materials representing a wide range of atomic numbers (Z = 3.5–73) were used. The experiment was carried out at the iodine Prague Asterix Laser System. The laser provided a 250 ps pulse with energy of 130 J at the third harmonic frequency (λ3 = 0.438 μm). To study the plasma stream configurations a four-frame X-ray pinhole camera was used. The electron temperature of the plasma in the near-surface target region was measured by means of an X-ray spectroscopy. The efficiency of the plasma energy transport to the target was determined via the crater volume measurement using the crater replica technique. The experimental results were compared with two-dimensional numerical simulations where the plasma dynamics was based on the one-fluid, two temperature model, including radiation transport in diffusive approximation and ionization kinetics. It was shown that the plasma expansion geometry plays an important role in the ablative plasma energy transfer into the target.